Geochemical implications from direct Rock-Eval pyrolysis of petroleum. (August 2020) - Scheeder, Georg; Weniger, Philipp; Blumenberg, Martin
Highlights: Rock-Eval was adapted for pyrolysis of oil. Oil composition index (OCI) defined from oil pyrograms. OCI increases with increasing thermal maturity. Unless affected by biodegradation and migration, maturity mainly controls OCI. Case study demonstrates that OCI holds information on kerogen-type. Abstract: The maximum burial depth and thermal maturity of a hydrocarbon source rock controls the generation of petroleum, and data on rock maturity are necessary for an understanding of a petroleum system. Rock-Eval pyrolysis is an established method to assess the hydrocarbon generation potential, the type of organic matter (kerogen type), but also the thermal maturity of hydrocarbon source rocks. Data on the thermal maturity of source rocks and/or of the generated hydrocarbons are, however, often lacking either, because (i) the source rock itself is not available or (ii) today's maturities cannot be directly linked to a generated petroleum, because petroleum generation and expulsion may have taken place at an earlier and less mature stage of the source rock. Indirect records of source rock maturities can be inferred from the physical properties of petroleum (e.g, API gravity), from biomarker abundances or from individual hydrocarbon ratios (including biomarkers). Using an adapted direct Rock-Eval pyrolysis approach for petroleum samples we present data from oils from the BGR petroleum archive. We distinguish between two hydrocarbon release-stages during Rock-Eval pyrolysis of which the first represents a vaporizable mid-molecular (S1oil ) fraction (< 400 °C; n -C15 -> n -C40 ) and the second (S2oil ) fraction (> 400 °C; > n -C40 ) most likely represents a residual higher-molecular weight petroleum fraction generating hydrocarbons by pyrolytic destruction. Using this program, we calculate an "Oil Composition Index" (OCI). Unless processes like biodegradation, evaporation or migration can affect OCI values, in a relatively well known petroleum system without major influences from these processes (the Gifhorn Trough in the Lower Saxony Basin [LSB] in Northern Germany), our data indicate that maturity of the source rock during expulsion is key for OCI. Application of Rock-Eval on a large set of oils from the entire LSB demonstrates that OCI values further hold information on the kerogen-type of the source rock (Wealden vs. Posidonia shales).